1981
DOI: 10.1177/000992288102000506
|View full text |Cite
|
Sign up to set email alerts
|

Teenage Pregnancy in Perspective

Abstract: In an effort to provide the clinician with suggestions for preventive and remedial approaches to adolescent pregnancy, the nature, medical, social, economic, and psychological aspects of the problem are reviewed and discussed. While the rate of adolescent pregnancy is declining, there are more than 560,000 deliveries to teenagers annually. Medical risks are significantly diminished by early and comprehensive prenatal care. The major complications continue to be social and economic. Lower I.Q.s in offspring of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The high percentage of women who have already had sexual and partnership experiences contradicts the explanation of the phenomenon as psycho-mental immaturity in terms of adolescent development aloneeven when this may play a major role in specific cases. Finally, so-called teenage pregnancies are a frequent problem that adolescents can generally overcome without concealing or denying their pregnancy [10,14,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The high percentage of women who have already had sexual and partnership experiences contradicts the explanation of the phenomenon as psycho-mental immaturity in terms of adolescent development aloneeven when this may play a major role in specific cases. Finally, so-called teenage pregnancies are a frequent problem that adolescents can generally overcome without concealing or denying their pregnancy [10,14,[17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Others described no differences in emergency department (ED) visits, hospitalizations, or immunizations for infants of younger and older mothers. [14][15][16] Limited available research suggested that the average adolescent mother has lower income than the average older mother, less education, and less awareness of her infant's medical needs, suggesting less ability to promote infant health. 2,8,[17][18][19] The association between infant health and socioeconomic status limits the usefulness of most studies of this issue, which typically rely on health care claims data that do not permit individual-level controls for characteristics such as education or income.…”
mentioning
confidence: 99%
“…20 21 For those sexually active teenagers who do not use contraception, there is a 90% probability of conceiving in 1 year, 14 although clearly the frequency of unprotected intercourse is relevant. 15 Lack of access, lack of confidence in discussing use with a partner and confusion about the law in relation to use of contraception among those under 16 years are thought to be important factors in understanding why teenagers may not use contraception, even when not actively planning a pregnancy. 14 Simply not thinking about contraception or believing that it (pregnancy) ''won't happen to me'' may also be important factors.…”
mentioning
confidence: 99%